A Flow Virometry Process for Detection of SARS-Cov-2 Proposed for Large-Scale Screening of COVID-19 Cases - Soni, Niraja; Pai, Puja; Kumar G., Raja Krishna; Prasad, Venkatesh; Dasgupta, Santanu; Bhadra, Bhaskar (International Journal of Scientific Research in Biological Sciences, 2020)
The coronavirus disease, COVID 19, caused by SARS-CoV-2 has spread rapidly over 210 countries and declared as pandemic by World Health Organization (WHO). WHO also emphasized on scaling-up testing capacity, followed by isolation of infected individuals, and contact tracing, as the "backbone" of managing the pandemic. Globally, the detection of SARS-CoV-2 in patients are done by RT-PCR and blood antibody-based testing. However, immediate expansion of the scale of screening is very important to cover major fraction of 1.3 billion population of India. We, therefore, propose a flow-cytometry based high-throughput screening systems for testing of COVID 19 cases. The swab-samples in viral transport media could be analyzed using ?indirect flow cytometry?, where virus particle binds to specific primary antibody and the resulted virus-antibody complex then binds to a fluorescent tagged secondary antibodies. The fluorescence signal can distinguish on a flow-channel to identify viral load in a test sample. In the present article, we have summarized a flow-virometry process for detection of various viruses and have proposed possible application of the process in screening of COVID 19.